Varicocele - Biyani, Chandra Shekhar (BMJ Publishing Group, 2009)
INTRODUCTION: Varicocele is estimated to affect 10% to 15% of men and adolescent boys. It usually occurs only on the left side, and is often asymptomatic. There is little evidence that varicocele reduces male fertility, although it is found in 12% of male partners of couples presenting with infertility and in 25% of men with abnormal semen analysis. METHODS AND OUTCOMES: We conducted a systematic review and aimed to answer the following clinical question: What are the effects of treatments in men with varicocele? We searched: Medline, Embase, The Cochrane Library, and other important databases up to May 2008 (Clinical Evidence reviews are updated periodically; please check our website for the most up-to-date version of this review). We included harms alerts from relevant organisations such as the US Food and Drug Administration (FDA) and the UK Medicines and Healthcare products Regulatory Agency (MHRA). RESULTS: We found 11 systematic reviews, RCTs, or observational studies that met our inclusion criteria. We performed a GRADE evaluation of the quality of evidence for interventions. CONCLUSIONS: In this systematic review we present information relating to the effectiveness and safety of the following interventions: embolisation, expectant management, sclerotherapy, and surgical ligation.